Metamorphic P–T–t evolution of mafic HP granulites in the northeastern segment of the Tarim Craton (Dunhuang block): Evidence for early Paleozoic continental subduction - He, Zhenyu; Zhang, Zeming; Zong, Keqing; Xiang, Hua; Klemd, Reiner (Lithos, 2014)
The Dunhuang block, which constitutes the northeastern segment of the Tarim Craton, is located between the Central Asian Orogenic Belt (CAOB) to the north and the Altyn-Qilian Orogenic Belt to the south. The present study reveals that the early Paleozoic HP mafic granulites from the Dunhuang block underwent four stages of metamorphism: prograde amphibolite-facies (M1), peak high-pressure (HP) granulite-facies (M2) and two late stages of amphibolite-facies retrograde metamorphism. Based on phase equilibrium modeling, P-T conditions of the four stages of metamorphism are estimated at 720-750. °C and 11-13. kbar, 760-800. °C and 14-16. kbar, 690-720. °C and 8-8.5. kbar, and at <. 6. kbar and <. 640. °C respectively. Peak granulite-facies metamorphism is characterized by a low geothermal gradient of ca. 16. °C/km. Zircon U-Pb dating shows that the HP granulite-facies metamorphism occurred at ca. 431. Ma and the early retrograde amphibolite-facies overprint at ca. 403. Ma. Thus the investigated mafic rocks here reveal a clockwise P-T-t path involving burial heating before peak granulite-facies metamorphism and subsequent decompression-cooling with an uplift rate of ca. 0.8. km/Ma. This, together with a continental affinity of the HP metamorphic rocks, indicates that the Dunhuang block experienced a collisional orogenesis during the early Paleozoic. © 2014 Elsevier B.V.
UnivIS-Import:2015-03-09:Pub.2014.nat.dgeo.IGM.c3geoc.metamo
Keywords: Beishan orogenic collage; CAOB; Dunhuang block; Early Paleozoic; HP granulite; P-T-t path